Classification and Description of Categorical Systems About Peer Socio-cognitive Interaction - Leguizamón, Romina (2020)
A Socio-constructivist psychology proposes the interactive nature of development and knowledge. In this sense, the analysis of socio-cognitive interaction has been a central aspect within this tradition.The systematic and reliable analysis of the interaction involves a great challenge since its complexity, dynamicity and multiplicity. The literature shows a wide variety of methodological proposals for the analysis of socio-cognitive interaction, ranging from more holistic approaches to more systematic approaches based on the construction of categories. The latter constitute the focus of interest of this work. The aim is to propose a classification and description of the variety of categorical systems usedin recent years for the analysis of socio-cognitive peer interaction. From a systematic review in different international databases, 24 categorical systems were selected and analyzed. The classification was based on two relevant elements in the definitionof a system of categories: (a) the unit of coding or analysis (molecular and molar); (b) the type of empirical indicator considered (predominantly linguistic, predominantly behavioral and mixed). The results suggest a predominance of linguistic molecular systems (50%), compared to molar and / or predominantly behavioral or mixed systems. These results are discussed from the concept of inter-subjectivity and the evolutionary-educational moment of the participants of the studies analyzed (primary level). At the same time, it concludes about the need to incorporate new molar systems that more faithfully reflect the emergent and irreducible nature of socio-cognitive.